A novel condition of mild electrical stimulation exerts immunosuppression via hydrogen peroxide production that controls multiple signaling pathway - Piruzyan, Mariam (PLoS One, 2020)
Different modes of exogenous electrical stimulation at physiological strength has been applied to various diseases. Previously, we extensively demonstrated the usability of mild electrical stimulation (MES) with low frequency pulse current at 55 pulses per second (MES(55)) for several disease conditions. Here we found that MES with high frequency pulse-current (5500 pulse per second; MES(5500)) suppressed the overproduction of pro-inflammatory cytokines induced by phorbol myristate acetate/ionomycin in Jurkat T cells and primary splenocytes. MES(5500) also suppressed the overproduction of inflammatory cytokines, improved liver damage and reduced mouse spleen enlargement in concanavalin-A-treated BALB/c mice. The molecular mechanism underlying these effects included the ability of MES(5500) to induce modest amount of hydrogen peroxide and control multiple signaling pathways important for immune regulation, such as NF-κB, NFAT and NRF2. In the treatment of various inflammatory and immune-related diseases, suppression of excessive inflammatory cytokines is key, but because immunosuppressive drugs used in the clinical setting have serious side effects, development of safer methods of inhibiting cytokines is required. Our finding provides evidence that physical medicine in the form of MES(5500) may be considered as a novel therapeutic tool or as adjunctive therapy for inflammatory and immune-related diseases.